2019
DOI: 10.1073/pnas.1900310116
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoparticle-based local translation reveals mRNA as a translation-coupled scaffold with anchoring function

Abstract: The spatial regulation of messenger RNA (mRNA) translation is central to cellular functions and relies on numerous complex processes. Biomimetic approaches could bypass these endogenous complex processes, improve our comprehension of the regulation, and allow for controlling local translation regulations and functions. However, the causality between local translation and nascent protein function remains elusive. Here, we developed a nanoparticle (NP)-based strategy to magnetically control mRNA spatial patterns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…mRNA drugs have emerged as a safe and efficacious strategy for protecting patients from infectious diseases and cancers owing to their advantages, including high efficiency, low side efficacy, and ease of manufacture. mRNAs display high therapeutic efficacy due to their continuous translation into encoded proteins/peptides compared to transient traditional protein/peptide drugs [69]. mRNA has been successfully transfected and produced an immune response in a dose-dependent manner [70].…”
Section: Mrna Vaccines As Anti-cancer Therapeuticsmentioning
confidence: 99%
“…mRNA drugs have emerged as a safe and efficacious strategy for protecting patients from infectious diseases and cancers owing to their advantages, including high efficiency, low side efficacy, and ease of manufacture. mRNAs display high therapeutic efficacy due to their continuous translation into encoded proteins/peptides compared to transient traditional protein/peptide drugs [69]. mRNA has been successfully transfected and produced an immune response in a dose-dependent manner [70].…”
Section: Mrna Vaccines As Anti-cancer Therapeuticsmentioning
confidence: 99%
“…It is possible that the spatial arrangement of translation complexes relative to other cell structures can serve as a factor that sets the desired orientation of higher-order protein complexes. Recently, such a mechanism was reconstituted in a cell lysate [ 228 ]: the authors were able to organize the structure of actin filaments in a certain way by localizing the transcripts encoding actin-binding protein using magnetic nanoparticles.…”
Section: Intracellular Transport Of Mrnas and Their Interaction With Cytoskeletal Elementsmentioning
confidence: 99%
“…A recent study reported how microtubule-based active nematic gels, in contact with a thermotropic liquid crystal, can have their orientation dictated by a magnetic field (29). As magnetic interactions can be contactless, remote controlled and can deeply penetrate into thick materials, it could be advantageous to manipulate directly the constitutive elements of the active gel, as it has been shown for other biomolecules (30)(31)(32). In our study, we developed a strategy to label kinesin motors with magnetic nanoparticles in order to perturb the dynamical properties of a microtubule active gel.…”
Section: Introductionmentioning
confidence: 99%